Narrative World, Rhetorical Logic, and the Voice of the Author in 4 Ezra - Stewart, Alexander E. (Journal of Biblical literature, 2013)
The relationship between the dialogues in the first three episodes of 4 Ezra and the visions and epilogue in the closing four episodes has challenged scholars for over a century. The inconclusiveness of the dialogues (episodes 1-3) along with the apparently different emphases in the visions and epilogue (episodes 4-7) has made it difficult for scholars to agree on the actual author's position. Who does the author want the reader to agree with: Ezra, Uriel, neither, or some combination of both? This article seeks to address these problems from a fresh perspective by studying the foundational narratives appealed to and presupposed in the worldviews of Ezra and Uriel in the dialogues, and by the visions in the second half of 4 Ezra. A concluding section will explore the answers provided by the author of 4 Ezra to the two dominant problems he raises in the book (the one/ many, and many/few) and will reflect on the rhetorical force of the book, the voice of the author, and the purpose of 4 Ezra. The narrative frame and flow of 4 Ezra solidly root the author's own convictions and theology in episodes 4 through 7. The author's primary purpose for the book is to renew Israel's faith in its covenant-keeping God and motivate the people to pursue righteousness through obedience to the law in the absence of a functioning temple.